The removal of plumbum and zinc using activated carbon - Asong, Angkat (2008)
This project was about removing heavy metal, Pb and Zn using activated carbon and to investigate the effect of activated carbon dosage and pH of heavy metal solution during the experiment. In the experiment, the effect of different particle size of activated carbon also being studied. The experiment was using different doses of activated carbon to investigate the removal of heavy metal. It was carried by adding different doses of activated carbon to stock solution. Besides, it was also tested at different value of pH, which was done by adding an amount of activated carbon that gives the best performance into different pH of stock solution to get the maximum heavy metal removal. The powdered and granular activated carbon (GAC) used to see the different effect. To get the maximum effect, the solution was well mixed using the orbital shaker for 1 hour at 30oC. Samples were taken after it mixed and analyzed using Atomic Absorption Spectrophotometer (AAS). From the result, pH 10 gives the highest removal percentage of the heavy metal which is 92.8% for zinc ion and 93.36% for plumbum ion. From the result also, the removal percentage of heavy metal ion was highest when 5g of activated carbon was added to both simulated waste water. The removal percentage was 47.2% for zinc ion and 62.68% for plumbum ion. The result also shows that the powdered activated carbon (PAC) can increase the percentage of heavy metal ion removal compare to GAC. The removal percentage was 95.2% when the PAC was used while 53.74% for GAC. As conclusion, we know that activated carbon dosage and pH totally influence the removal of heavy metal ion.-Author